A microstructural and mechanical behavior study of heterogeneous P91 welded joint. (August 2020) - Kumar, Sanjeev; Pandey, Chandan; Goyal, Amit
Abstract: The current work has been performed to characterize the heterogeneous P91 welded joint. The gas tungsten arc welded (GTAW) P91 welds joint has been prepared using the dissimilar Inconel 617 filler. The P91 welded plates have been subjected to post-weld normalizing and tempering (PWNT) heat treatments for varying normalizing temperature in the range of 950–1150 °C. To homogenize the microstructure across the welded joint, tempering has been performed at 760 °C for 2 h for each normalized conditions. The tensile and microhardness tests have been conducted to determine the mechanical properties of the welded joint in as-welded and heat-treated conditions. The microstructure characterization has been performed for the weld fusion zone (WFZ) and efforts have been made to develop a relation between microstructure evolutions and mechanical behavior of the welded joint. Microstructure analysis was carried out with optical and field scanning electron microscope (FESEM). The optimum combination of strength and ductility was obtained for the sample heat-treated at 1050 °C for 40 min (normalized)+760 °C/2 h (tempering). The lower strength was obtained for the Inconel 617 filler as compared to P91 filler, while ductility obtained for Inconel 617 filler was higher than that of P91 filler. Highlights: Role of the dissimilar Inconel 617 filler on microstructural behavior of the P91 welded joint. Study on the effect of the dissimilar filler on the mechanical performance of the P91 welded joint. Study on effect of the heat treatment on microstructure evolution in the weld fusion zone and HAZ. Role of the filler and heat treatment on homogenization of the microstructure across the welded joint.